A manifestação messiânica de Jesus no Sábado: um estudo bíblico-teológico de Lc 4,16-21 - Silva, Moisés da (2020)
This dissertation aims to demonstrate that Jesus is the scatological Messiah announced by the prophets. Passes through the midrash methodological criteria of promise and fulfillment, by the aggadic dimension, in addition to a narrowing through critics, according to the codes. He then reflected on the journey of Jesus, who, after his baptism in Jordan, had returned to Nazareth as annointed by the Holy Spirit and entered the synagogue on Saturday, announcing, through Isahian word, as The Messiah. In Jesus’s return to the synagogue, the evangelist Lucas, highlights the Sabbath day as locus theologicus. And yet, it underlines "today" as the time when the Jesuit missionary program is fulfilled and proclaims the year favorable year of the Lord. In this way, hope is proclaimed to the marginalized who are reached by the mercy of Adonai manifested in Jesus, the scatological Messiah who evangelizes the poor, proclaims liberation to the captives, to the blind the recovery of sight, to the oppressed freedom and announces the jubilee year by the Lord